Factors associated with falls among hospitalized and community-dwelling older adults: the APPCARE study - Bally, Esmée L. S.; Ye, Lizhen; van Grieken, Amy; Tan, Siok Swan; Mattace-Raso, Francesco; Procaccini, Elena; Alhambra-Borrás, Tamara; Raat, Hein (Frontiers in Public Health, 2023)
Background Falls are a leading cause of disability. Previous studies have identified various risk factors for falls. However, contemporary novel research is needed to explore these and other factors associated with falls among a diverse older adult population. This study aims to identify the factors associated with falls among hospitalized and community-dwelling older adults. Methods Cross-sectional data from the ‘Appropriate care paths for frail elderly people: a comprehensive model’ (APPCARE) study were analyzed. The study sample consisted of hospitalized and community-dwelling older adults. Falling was assessed by asking whether the participant had fallen within the last 12 months. Multivariable logistic regression models were used to evaluate associations between socio-demographic characteristics, potential fall risk factors and falls. Results The sample included 113 hospitalized (mean age = 84.2 years; 58% female) and 777 community-dwelling (mean age = 77.8 years; 49% female) older adults. Among hospitalized older adults, loneliness was associated with an increased risk of falls. Associations between female sex, secondary education lever or lower, multimorbidity, a higher score on limitations with activities of daily living (ADL), high risk of malnutrition and falling were found among community-dwelling participants. Conclusion The results of this study confirm the multi-factorial nature of falling and the complex interaction of risk factors. Future fall prevention programs could be tailored to the needs of vulnerable subpopulations at high risk for falls.